Analisis Gamification Shopee.com Sebagai Media Pemasaran Terhadap EWOM, Positive Emotion, & Repurchase Intention (Pada Aplikasi Shopee.com) - Chrisnathaniel, Hendy; Hartini, Sri; Rahayu, Sari Puji (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2021)
This study aims to explore the influence of Shopee.com gamification as a marketing media for EWOM, positive emotion, and repurchase intention. Researchers emphasize on Shopee as one of the e-commerce that is first ranked with the number of monthly web visitors, and first ranked on the Appstore and Playstore in Indonesia. This study uses a questionnaire distributed online to 170 respondents, with criteria as the